Source apportionment of PM2.5 in Thailand’s deep south by principal component analysis and impact of transboundary haze - Phatsarakorn Chaisongkaew; Racha Dejchanchaiwong; Muanfun Inerb; Napawan Mahasakpan; Nobchonnee Nim; Hisam Samae; Panich Intra; John Morris; Thammasin Ingviya; Thanathip Limna; Perapong Tekasakul (Environmental Science and Pollution Research, 2023)
dominated throughout the year. The effects of external sources, especially the transboundary haze from peatland fires, were significantly enhanced, because the background air in the study locations was generally clean. PCA indicated that vehicle emission, local biomass burning, and secondary particles played a key role during normal period, whereas open biomass burning dominated during the haze phenomena. This was consistent with the OC/EC and PAH diagnostic ratios. Backward trajectories confirmed that the sources of PM during the haze period were predominantly peatland fires in Sumatra, Indonesia, due to southwest wind.
Keywords: Atmospheric chemistry and aerosols; Air Quality and Health Impacts; Atmospheric and Environmental Gas Dynamics